Studi Asosiasi Genom (GWAS) Komponen Tandan Populasi Interspesifik Elaeis oleifera dan Elaeis guineensis - Heri Adriwan Siregar; Edy Suprianto; Sujadi Sujadi; Hernawan Y Rahmadi; Mohamad Arif; Retno Diah Setiowati; Nanang Supena; Rokhana Faizah; Sri Wening; Yurna Yenni; Abdul Razak Purba (Pusat Penelitian Kelapa Sawit, 2021)
The oil palm breeding program for the species Elaeis guineensis and the backcross Elaeis oleifera is running slowly because oil palm is an annual plant. Therefore, it is necessary to have an alternative approach that can accelerate the oil palm breeding program. The SNP (single nucleotide polymorphism) genome-wide approach was then used to study the association between 18 phenotypes of bunch component in oil palm germplasm of E. oleifera from Suriname and Brazil Coari, some interspecific hybrids and some elite progeny of E. guineensis. The genotyping by sequencing (GBS) analysis produced a total of 459 million or approximately 798 thousand reads per sample and 3,252 SNPs were eligible for 456 genotypes. Using various association models, eleven normalized phenotypic data showed significant associations with 29 SNPs. Based on the annotations, 17 SNPs were related to genes wtih certain biological functions. Three SNPs were found to be at the exon of a gene, namely SNP4416, SNP349 and SNP3865, while the other 15 SNPs were at the intragenic to a gene. Four SNPs are common SNPs in phenotypes C16:0 and C18:1 as weel as in C20 0 and C20:1. This research shows the potential of SNPs that can be used as an alternative approach to E. oleifera backcross breeding, although further research is needed for validation purposes.